Case Report: Thoracoscopic treatment of infradiaphragmatic pulmonary sequestration and intrathoracic kidney associated with congenital diaphragmatic hernia - Guo, Rui; Dong, Chunhua; Zhai, Yunpeng; Zhao, Huashan; Lv, Longfei; Zhang, Shisong (Frontiers in Pediatrics, 2024)
Background Congenital pulmonary sequestration is a rare lung anomaly that can be classified as intralobar pulmonary sequestration or extralobar lung sequestration (ELS). Infradiaphragmatic pulmonary sequestration is a rare type of ELS. Furthermore, intrathoracic kidney (ITK) is a rare disease that can be associated with a congenital diaphragmatic hernia (CHD) in 0.25% of cases. We report the first case of infradiaphragmatic pulmonary sequestration and ITK associated with CDH in a child. Case report and management The patient, male, aged 6 months, visited our hospital 2 months prior due to shortness of breath. Based on chest ultrasonography and enhanced computed tomography (CT) examination, infradiaphragmatic pulmonary sequestration and ITK were considered to be associated with CDH. The patient was admitted to our hospital for treatment. After admission, his blood pressure was 85/61 mmHg, there was no hematuria or proteinuria, creatinine was 14 µmol/L, and urea nitrogen was 2.96 mmol/L, all of which showed no abnormalities. A complete preoperative examination was performed prior to surgical treatment. Thoracoscopy revealed that the right kidney had herniated into the chest cavity on the posterolateral side of the diaphragm. The right kidney was returned to the abdominal cavity, the hernia sac was opened, and a bright red lesion tissue with clear boundaries and an abnormal blood vessel supply was observed. After cutting off the abnormal blood vessels, LigaSure TM was used to remove the diseased tissue, and the renal fat sacs and renal tissue were visible. Intermittent suturing of the hernia ring was performed to seal the diaphragmatic hernia. Postoperative pathological examination revealed infradiaphragmatic pulmonary sequestration. The postoperative recovery of the patient was smooth, and a chest CT scan at 2 months showed that the right kidney had returned to the abdominal cavity and the right diaphragm was in the normal position. Conclusion Infradiaphragmatic pulmonary sequestration and ITK associated with CDH is extremely rare. A diagnosis and appropriate surgical planning can be developed using enhanced CT. For infradiaphragmatic pulmonary sequestration located at the top of the hernia sac in CHD, thoracoscopic resection of the infradiaphragmatic pulmonary sequestration and repair of the diaphragmatic hernia is feasible and effective.